Regulation of plant ER oxidoreductin 1 (ERO1) activity for efficient oxidative protein folding - Matsusaki, Motonori (J Biol Chem, 2019)
In the endoplasmic reticulum (ER), ER oxidoreductin 1 (ERO1) catalyzes intramolecular disulfide-bond formation within its substrates in coordination with protein-disulfide isomerase (PDI) and related enzymes. However, the molecular mechanisms that regulate the ERO1–PDI system in plants are unknown. Reduction of the regulatory disulfide bonds of the ERO1 from soybean, GmERO1a, is catalyzed by enzymes in five classes of PDI family proteins. Here, using recombinant proteins, vacuum-ultraviolet circular dichroism spectroscopy, biochemical and protein refolding assays, and quantitative immunoblotting, we found that GmERO1a activity is regulated by reduction of intramolecular disulfide bonds involving Cys-121 and Cys-146, which are located in a disordered region, similarly to their locations in human ERO1. Moreover, a GmERO1a variant in which Cys-121 and Cys-146 were replaced with Ala residues exhibited hyperactive oxidation. Soybean PDI family proteins differed in their ability to regulate GmERO1a. Unlike yeast and human ERO1s, for which PDI is the preferred substrate, GmERO1a directly transferred disulfide bonds to the specific active center of members of five classes of PDI family proteins. Of these proteins, GmPDIS-1, GmPDIS-2, GmPDIM, and GmPDIL7 (which are group II PDI family proteins) failed to catalyze effective oxidative folding of substrate RNase A when there was an unregulated supply of disulfide bonds from the C121A/C146A hyperactive mutant GmERO1a, because of its low disulfide-bond isomerization activity. We conclude that regulation of plant ERO1 activity is particularly important for effective oxidative protein folding by group II PDI family proteins.